2022
DOI: 10.3389/fpsyg.2022.952549
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing microgame adoption among secondary school mathematics teachers supported by structural equation modelling-based research

Abstract: Microgames are rapidly gaining increased attention and are highly being considered because of the technology-based media that enhances students’ learning interests and educational activities. Therefore, this study aims to develop a new construct through confirmatory factor analysis, to comprehensively understand the factors influencing the use of microgames in mathematics class. Participants of the study were the secondary school teachers in West Java, Indonesia, which had a 1-year training in microgames devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 95 publications
0
12
1
Order By: Relevance
“…Schools should consider incorporating students' self-regulated learning into their curriculum. By using classroom games and dynamic mathematics software (Wijaya et al, 2020(Wijaya et al, , 2022a, teachers can let students develop a better understanding of self-regulation strategies and stimulate their selfregulation learning. Mathematics teachers should provide specialized instruction and related training activities tailored to students with different self-regulated learning profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Schools should consider incorporating students' self-regulated learning into their curriculum. By using classroom games and dynamic mathematics software (Wijaya et al, 2020(Wijaya et al, , 2022a, teachers can let students develop a better understanding of self-regulation strategies and stimulate their selfregulation learning. Mathematics teachers should provide specialized instruction and related training activities tailored to students with different self-regulated learning profiles.…”
Section: Discussionmentioning
confidence: 99%
“…This is because ESD teaching framework is in favor of studentcentered, collaborative, action-oriented and interdisciplinary teaching approach (UNESCO, 2017b(UNESCO, , 2020. While studies that support the use of microgames have focused on a singlesubject teaching approach (Seidler, 2021;Rahmadi et al, 2022;Wijaya et al, 2022), the present study went further to reveal the potential of microgames to facilitate interdisciplinary teaching approach. Therefore, there is a need to consider microgames as teaching resources in the implementation of ESD.…”
Section: Discussionmentioning
confidence: 96%
“…by providing engaging learning experiences, simulation games can support the whole learning process, because they provide a situation where the learner can directly acquire new knowledge and skills." Moreover, studies have revealed that mathematics (Rahmadi et al, 2022;Wijaya et al, 2022) and language (Seidler, 2021) are among the subjects whose teaching and learning could benefit from the use of microgames in the classroom. Therefore, this call for educators to consider microgames as one of the useful teaching resources.…”
Section: Introductionmentioning
confidence: 99%
“…Schools, where teachers work, ought to increase subjective well-being alongside reducing and managing stress levels caused by many factors, such as engagement [27]. Therefore, their job becomes more fun and innovation can be carried out with learning media or models for better performance as 21st century mathematics teachers [108,109]. This study aimed to: (1) determine the factors related to mathematics teachers' stress levels and subjective well-being, and (2) observe those with the greatest significant effect on improving well-being and reducing stress levels.…”
Section: Discussionmentioning
confidence: 99%